Vicinity condition of online examination : does it affect the academic performances of pre-university students? - Nurul Najidah Mohamed,; Siti Norziahidayu Amzee Zamri,; Nurulhuda Mohammad Yusoff,; Noor Asidah Mohamed,; Fauziah Ab. Wahab,; Salmiah Jamal Mat Rosid,; Siti Maisarah Aziz,; Aida Othman,; Sharifah Wajihah Wafa Syed Saadun Tarek Wafa,; Siti Noor Syuhada Muhammad Amin,; Azma Malek,; Nurul Asma Hasliza Zulkifly, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Physical attendance of students in a hall for examinations is no longer being practiced during the global pandemic of Coronavirus disease 2019 (Covid-19). Most universities, including Universiti Sultan Zainal Abidin (UniSZA) have adapted to online exams. This paper presents an analysis of online final examination performances of 251 students from the Science and Medicine Foundation Centre, UniSZA who completed foundation for 2019/2020 and 2020/2021 intake sessions. The objective of this research is to compare the final scores of Semester 2 for the students from both sessions, if there is a significant difference between academic performance by taking online examination at home for 2019/2020 intake session and at the university for 2020/2021 intake session based on the subjects of Mathematics II, Physics II, Chemistry II, Biology II and Information Technology II. The z-test was performed to compare mean scores for each subject for both intake sessions using Microsoft Excel worksheet. According to the mean value, students achieved higher score in Biology II, Chemistry II and Information Technology II by taking examination at hostel. Meanwhile, Physics II and Mathematics II subjects shows that the score are higher while taking examination at home. The p-value for each subject is computed, and the result is less than 0.025. The null hypothesis is then rejected.